Identificación de los plaguicidas utilizados en la producción de hortalizas en la parroquia Imbaya cantón Antonio Ante provincia de Imbabura 2017 - Lagos Brusil, Marco Alirio (2018)
Summary For the development of the document we seek the identification of the pesticides used in the production of vegetables in the parish of Imbaya, canton Antonio Ante, province of Imbabura located at the geographic coordinates: Latitude North 00 ° 25 '26 "; Longitude West 78 ° 19 '10 "and at an altitude of 2350 m.s.n.m. Its climatic conditions report an average annual temperature of 20 ° C, with an annual rainfall of 1200 mm, In the identification of the problem we use the information collected with the help of questions addressed to the farmers of the sector, which were support material in the development of the document, interpreting the data obtained with a descriptive statistic, with the use of graphics that were expressed in percentages percentages in which it was determined that the crop was mostly adopted by farmers for its cultivation, was identified the agrochemical that is most frequently used in crops, its application toxicity and health risks The problem that I highlight most in the research is the search of the most used pesticides by the vegetable producers, identifying their application and dose of work, specifying in which moments of the phenological stage of the crop are applied and if they perform an adequate rotation, without create resistance to the pathogens that attack.